Lamin A/C loss promotes R-loop-mediated genomic instability and poor survival in small-cell lung cancer - Christopher W. Schultz; Sourav Saha; Anjali Dhall; Yang Zhang; Parth Desai; Lorinc S. Pongor; David A. Scheiblin; Valentin Magidson; Ravi P. Shuklah; Robin Sebastian; Umeshkumar M. Vekariya; Shahbaz Ahmed; et al. (Proceedings of the National Academy of Sciences, 2025)
Lamin A/C ( LMNA ), a key component of the nuclear envelope, is essential for maintaining nuclear integrity and genome organization [W. Xie et al. , Curr. Biol. 26 , 2651–2658 (2016)]. While LMNA dysregulation has been implicated in genomic instability across cancer and aging, the underlying mechanisms remain poorly understood [S. Graziano et al. , Nucleus 9 , 258–275 (2018)]. Here, we define a mechanistic role for LMNA in preserving genome stability in small-cell lung cancer (SCLC), a malignancy marked by extreme genomic instability [N. Takahashi et al. , Cancer Res. Commun. 2 , 503–517 (2022)]. LMNA depletion promotes R-loop accumulation, transcription-replication conflicts, replication stress, DNA breaks, and micronuclei formation. Mechanistically, LMNA deficiency disrupts nuclear pore complex organization, specifically reducing phenylalanine-glycine (FG)-nucleoporin incorporation, resulting in impaired RNA export and nuclear retention of RNA. LMNA expression is repressed by EZH2 and reexpressed during SCLC differentiation from neuroendocrine (NE) to non-NE states, and low LMNA levels correlate with poor clinical outcomes. These findings establish LMNA as a key regulator of nuclear transport and genome integrity, linking nuclear architecture to SCLC progression and therapeutic vulnerability.